A trans‐outer membrane porin‐cytochrome protein complex for extracellular electron transfer by Geobacter sulfurreducens PCA. Issue 6 (24th September 2014) - Liu, Yimo; Wang, Zheming; Liu, Juan; Levar, Caleb; Edwards, Marcus J.; Babauta, Jerome T.; Kennedy, David W.; Shi, Zhi; Beyenal, Haluk; Bond, Daniel R.; Clarke, Thomas A.; Butt, Julea N.; et al.
Summary The multi‐heme, outer membrane c‐type cytochrome (c‐Cyt) OmcB of Geobacter sulfurreducens was previously proposed to mediate electron transfer across the outer membrane. However, the underlying mechanism has remained uncharacterized. In G. sulfurreducens, the omcB gene is part of two tandem four‐gene clusters, each is predicted to encode a transcriptional factor (OrfR/OrfS), a porin‐like outer membrane protein (OmbB/OmbC), a periplasmic c‐type cytochrome (OmaB/OmaC) and an outer membrane c‐Cyt (OmcB/OmcC) respectively. Here, we showed that OmbB/OmbC, OmaB/OmaC and OmcB/OmcC of G. sulfurreducens PCA formed the porin‐cytochrome (Pcc) protein complexes, which were involved in transferring electrons across the outer membrane. The isolated Pcc protein complexes reconstituted in proteoliposomes transferred electrons from reduced methyl viologen across the lipid bilayer of liposomes to Fe(III)‐citrate and ferrihydrite. The pcc clusters were found in all eight sequenced Geobacter and 11 other bacterial genomes from six different phyla, demonstrating a widespread distribution of Pcc protein complexes in phylogenetically diverse bacteria. Deletion of ombB‐omaB‐omcB‐orfS‐ombC‐omaC‐omcC gene clusters had no impact on the growth of G. sulfurreducens PCA with fumarate but diminished the ability of G. sulfurreducens PCA to reduce Fe(III)‐citrate and ferrihydrite. Complementation with the ombB‐omaB‐omcB gene cluster restored the ability of G. sulfurreducens PCA to reduce Fe(III)‐citrate and ferrihydrite.